1990
DOI: 10.1159/000276167
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Polyposis as a Risk Factor for Hypertension

Abstract: Arterial hypertension was found in 78 of 224 consecutive patients operated for nasal polyposis. An exacerbated degree of hypertension was significant in groups aged above 50 years. In total, 46% of patients whose nasal polyposis was of a duration of more than 10 years suffered from hypertension. Fifty of 78 patients developed hypertension after nasal polyposis was established and the mean duration time from polyposis to hypertension was 11.1 years. Hypertension was established in 50% of patients suffering from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…14,15 In a study of 27 patients with NP and hospitalized for a polypectomy, a correlation was found between the duration of obstruction and blood pressure (BP); it was also observed that patients who snored had higher BP values than those who did not, and that the mean values for nocturnal decline in BP and heart rate were less marked before surgery than after surgery. Oxygen saturation increased and catecholamines decreased only after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 In a study of 27 patients with NP and hospitalized for a polypectomy, a correlation was found between the duration of obstruction and blood pressure (BP); it was also observed that patients who snored had higher BP values than those who did not, and that the mean values for nocturnal decline in BP and heart rate were less marked before surgery than after surgery. Oxygen saturation increased and catecholamines decreased only after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may constitute a rationale for studies designed to further analyse the relationships between NP, QOL and sleep disorders, because NP has not only been shown to badly affect the patient's quality of life and sleep as a chronic nasal condition; some studies suggest that sleep disturbance may lead, in chronic conditions, to complications such as arterial hypertension. 14,15 In a study of 27 patients with NP and hospitalized for a polypectomy, a correlation was found between the duration of obstruction and blood pressure (BP); it was also observed that patients who snored had higher BP values than those who did not, and that the mean values for nocturnal decline in BP and heart rate were less marked before surgery than after surgery. Oxygen saturation increased and catecholamines decreased only after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal airflow is known to have an effect on breathing during sleep in humans [19] and thus may be interesting to look at in patients with OSAS [13]. Previous data show that an elevated nasal resistance is common among patients with OSAS [4, 13] and may be caused by a hypertrophy of the lower turbinates [16].…”
Section: Discussionmentioning
confidence: 99%
“…Nasal airflow is known to have an effect on breathing during sleep in humans [19] and thus may be interesting to look at in patients with OSAS [13]. Previous data show that an elevated nasal resistance is common among patients with OSAS [4, 13] and may be caused by a hypertrophy of the lower turbinates [16]. In patients with seasonal allergic rhinitis, an increase of apneas and arousals and a decrease of slow wave sleep could be shown during season compared with polysomnographical parameters in phases without rhinitic complaints [15, 19].…”
Section: Discussionmentioning
confidence: 99%